ANALISIS SEMIOTIKA MAKNA KATA APATEU PADA LIRIK LAGU “APT.” KARYA ROSÉ & BRUNO MARS - Rahmatika Putri Supuasari; Muadz Muadz (Solidaritas, 2025)
The song “APT.” is a collaboration between Rosé and Bruno Mars that went viral and gained significant attention from global listeners. However, the song has also sparked several controversies, such as its ban in South Korea for allegedly distracting students from their studies, the emergence of hoaxes in Malaysia, and debates surrounding the true meaning of the word apateu in the song’s lyrics. The song features playful, ambiguous lyrics that are repeated, leading to various interpretations and diverse reactions from listeners, especially regarding the actual meaning of the word apateu in the song “APT.” by Rosé and Bruno Mars. This study aims to uncover the true meaning of the word apateu in the lyrics of “APT.” by Rosé and Bruno Mars. The research method used is qualitative descriptive research. The semiotic analysis theory applied is that of Ferdinand de Saussure. The concepts used in this study are the signifier and the signified. The signifier in this case is the word apateu in the lyrics of “APT.” by Rosé and Bruno Mars. The signified functions to represent the concept of the signifier, which is the actual meaning. The relationship between the signifier and the signified must be interconnected to produce meaning from the sign. The true meaning is obtained through interpretation, based on primary and secondary data. The data collection techniques used are documentary and literature study. The interpretations of the word apateu are as follows: apateu as an apartment, the apateu game, and apartheid. These three interpretations, after being analyzed, will reveal the true meaning of the word apateu in the lyrics of “APT.” by Rosé and Bruno Mars. Keywords: Apateu, Analysis, Semiotics, Signs